2022
DOI: 10.1017/jfm.2022.529
|View full text |Cite
|
Sign up to set email alerts
|

Vortex ring connection to a free surface

Abstract: We perform numerical simulations of the interaction between a vortex ring and a free surface, and provide a new interpretation of the mechanism by which the vortex ring connects to the free surface. Large vorticity gradients at the free surface result in the diffusion of surface-tangential vorticity out of the fluid. This is accompanied by the diffusion of opposite-signed surface-normal vorticity away from the connection line, along the free surface, which results in the attachment of the vortex ring to the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 40 publications
(199 reference statements)
0
26
0
Order By: Relevance
“…The viscous term in (2.27) describes changes to the surface-normal vorticity that occur as a consequence of the diffusion of surface-tangential vorticity across the boundary. We have previously shown that this representation clearly illustrates how the kinematic condition that vortex lines do not end in the fluid is maintained (Terrington et al 2021(Terrington et al , 2022bTerrington, Hourigan & Thompson 2022a). For example, in the case of vortex ring connection to a free surface (Terrington et al 2022a), the diffusion of tangential vorticity out of the fluid (breaking open of vortex lines) coincides with the appearance of new surface-normal vorticity in the free surface (attachment of vortex lines to the boundary).…”
Section: Boundary Conditions For Surface-normal Vorticitymentioning
confidence: 75%
See 1 more Smart Citation
“…The viscous term in (2.27) describes changes to the surface-normal vorticity that occur as a consequence of the diffusion of surface-tangential vorticity across the boundary. We have previously shown that this representation clearly illustrates how the kinematic condition that vortex lines do not end in the fluid is maintained (Terrington et al 2021(Terrington et al , 2022bTerrington, Hourigan & Thompson 2022a). For example, in the case of vortex ring connection to a free surface (Terrington et al 2022a), the diffusion of tangential vorticity out of the fluid (breaking open of vortex lines) coincides with the appearance of new surface-normal vorticity in the free surface (attachment of vortex lines to the boundary).…”
Section: Boundary Conditions For Surface-normal Vorticitymentioning
confidence: 75%
“…For the oblique interaction between a vortex ring and a flat free-slip wall (Balakrishnan, Thomas & Coleman 2011), or a clean free surface Song et al 1991;Lugt & Ohring 1994;Gharib & Weigand 1996;Ohring & Lugt 1996;Zhang, Shen & Yue 1999;Terrington et al 2022a), a phenomenon known as vortex connection occurs. Surface-tangential vorticity from the upper part of the vortex ring diffuses out of the fluid at the free-slip boundary, causing the vortex ring to open up and attach to the surface.…”
Section: Vortex Ring Interactions With a Partial-slip Boundarymentioning
confidence: 99%
“…Finally, the L–H interpretation clearly illustrates how the kinematic condition that vortex lines do not end inside the fluid is maintained during viscous processes such as vortex reconnection (Terrington et al. 2021), or the connection of a vortex ring to a free surface (Terrington, Hourigan & Thompson 2022 a ). In addition, Eyink (2021) has shown that the Huggins tensor leads to a generalised Josephson–Anderson relation between the drag on a finite solid body and the vorticity flux.…”
Section: Enstrophy Dynamicsmentioning
confidence: 99%
“…2021), and for the interaction between a vortex ring and a free surface (Terrington et al. 2022 a ). Even if the L–H and L–P interpretations of enstrophy dynamics are quantitatively similar for highly inertial flows, only the L–H interpretation of enstrophy dynamics is consistent with the L–H interpretation of vorticity dynamics.…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation